2011
DOI: 10.1002/ajpa.21635
|View full text |Cite
|
Sign up to set email alerts
|

Does skeletal anatomy reflect adaptation to locomotor patterns? cortical and trabecular architecture in human and nonhuman anthropoids

Abstract: Although the correspondence between habitual activity and diaphyseal cortical bone morphology has been demonstrated for the fore- and hind-limb long bones of primates, the relationship between trabecular bone architecture and locomotor behavior is less certain. If sub-articular trabecular and diaphyseal cortical bone morphology reflects locomotor patterns, this correspondence would be a valuable tool with which to interpret morphological variation in the skeletal and fossil record. To assess this relationship,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
139
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(150 citation statements)
references
References 92 publications
(116 reference statements)
11
139
0
Order By: Relevance
“…Griffin et al (16) also found significantly lower BV/TV in the human first and second metatarsal heads compared with hominoid primates. The results of these studies are corroborated by work on the hominoid calcaneus (17), the anthropoid proximal femur (18), and several other clinical studies of femoral head trabecular bone architecture in contemporary adult humans (21-24). The results of these studies suggest that relative trabecular bone volume in the axial skeleton and lower limbs is significantly lower in modern humans compared with quadrupeds, despite the legs and vertebral column bearing a higher proportion of body mass and peak substrate reaction forces during bipedal locomotion (25)(26)(27).…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Griffin et al (16) also found significantly lower BV/TV in the human first and second metatarsal heads compared with hominoid primates. The results of these studies are corroborated by work on the hominoid calcaneus (17), the anthropoid proximal femur (18), and several other clinical studies of femoral head trabecular bone architecture in contemporary adult humans (21-24). The results of these studies suggest that relative trabecular bone volume in the axial skeleton and lower limbs is significantly lower in modern humans compared with quadrupeds, despite the legs and vertebral column bearing a higher proportion of body mass and peak substrate reaction forces during bipedal locomotion (25)(26)(27).…”
supporting
confidence: 59%
“…Human proximal femora were scanned on the OMNI-X HD600 microcomputed tomography scanner (Varian Medical Systems) at the Center for Quantitative Imaging, Pennsylvania State University. All nonhuman primates included in the study were scanned at the Center for Quantitative Imaging or at the University of Texas at Austin's High-Resolution X-Ray Computed Tomography Facility (18,52,(64)(65)(66). Voxel dimensions ranged from 0.0068 and 0.0687 mm, depending on size of the specimen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative studies characterizing the microarchitecture of trabecular bone have consistently found that humans have a lower bone volume fraction (BV/TV) than chimpanzees. Whether in the humeral head (Shaw and Ryan, 2012;Scherf et al, 2013), first metacarpal head (Lazenby et al, 2011), thoracic vertebra (Cotter et al, 2011), femoral head (Shaw and Ryan, 2012), calcaneal body (Maga et al, 2006), talar body (DeSilva and Devlin, 2012), or medial metatarsal heads (Griffin et al, 2010), humans consistently possess lower BV/TV than chimpanzees. Under the Achilles tendon insertion, however, we found a trend towards slightly higher BV/TV in humans than in chimpanzees, though this trend was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if our model for how the Achilles tendon loads calcaneal trabecular bone is correct, then our findings contradict some predictions of Wolff's "Law." Although many have found evidence for trabecular bone adaptation to changes in diet and hormones (Hodgkinson et al, 1978;Reeve et al, 1980;Devlin et al, 2010), and loading (Pontzer et al, 2006;Barak et al, 2011), others (Fajardo et al, 2007;Ryan and Walker, 2010;Shaw and Ryan, 2012;DeSilva and Devlin, 2012) have found the relationship between trabecular bone and inferred mechanical loading in primates to be more complicated. Although trabecular bone clearly is responsive to a variety of factors, Achilles tendon length may not affect trabecular properties as we had predicted.…”
Section: Discussionmentioning
confidence: 99%